Sustainability principles of the community-based tourism in Gemblung market - Rahmasari, Rizki; Wibawa, Samodra (Jurnal Pariwisata Pesona, 2022)
This study aims to determine the extent to which the causative principles of community-based tourism (CBT) have been applied in the management of Pasar Gemblung, a traditional market in Magelang Regency. Through a descriptive-qualitative approach, this study finds that the principles of CBT have been applied, so that the tourism market is expected to be sustainable. The driving factor for this principle is access to natural resources, market demand, the capacity of human resources, and employees, the inhibiting factor is access to resources and activities with other community activities. In order to make Pasar Gemblung better, the manager needs to open wider communication with residents, conduct promotions to increase the number of visitors and attract investors, and invite residents from other villages to be involved on a limited basis. For further research on this topic, we suggest deepening the aspects of local culture and its educational aspects.